Using plant-bivalve inter-specific facilitation to enhance coastal restoration - Wellman, Emory H (East Carolina University, 2021)
Salt marshes and oyster reefs are critical ecosystems which are being lost or degraded at an alarming pace around the world. Current restoration efforts are insufficient to compensate for past and current habitat degradation, with restoration often ending in failure or only partial recovery. Increasingly, ecologists are calling for the inclusion of facilitation in coastal restoration efforts as a method to bolster success. Facilitation is a positive interaction in which a habitat modifier reduces local abiotic or biotic stressors, allowing organisms which were previously excluded to persist. Inter-specific positive interactions are predicted to be particularly important in areas of high physical stress.In North Carolina, fringing oyster reefs and salt marsh vegetation facilitate each other's growth and persistence through attenuation of wave energy and substrate stabilization. These positive interactions represent a promising method to address pressing issues in coastal restoration, specifically, marsh restoration in environments stressed by high wave energy and excessive nutrient enrichment. To date, coastal restoration has largely failed to incorporate the benefits of positive interactions, despite research indicating that such facilitation may increase restoration success.I examined the ability of oyster reefs to mitigate hydrodynamic and nutrient enrichment stress on marsh vegetation (smooth cordgrass, Spartina alterniflora) in two studies at an eroding salt marsh in Beaufort, North Carolina. In Study 1, I constructed restored oyster reefs from two restoration substrates (Oystercatcher, OC; and shell bags, SB) on low- and high-energy shorelines, and compared their abilities to mitigate shoreline retreat, accrete and retain marsh sediment, and promote robust oyster communities. In Study 2, I investigated whether oyster reef presence can mitigate detrimental impacts of nutrient over-enrichment by transplanting and experimentally fertilizing S. alterniflora at a subset of the OC reef sites, comparing their growth and survival to that at control non-reef sites. Study 1 took place from May 2018 to August 2020, while Study 2 occurred in Summer 2019, with each study period including at least one extreme storm event (i.e. hurricane or tropical storm). In Study 1, constructed reefs mitigated marsh retreat on both shorelines, with the OC reefs outperforming SB reefs on the high-energy shoreline. SB reefs on that shoreline were severely damaged by storm events, while OC reefs on both shorelines exhibited steady oyster recruitment and growth. OC reefs hosted higher densities of larger oysters. In Study 2, transplanted vegetation experienced high rates of mortality, which were impacted by a complex interaction between elevation, fertilization, and reef presence. Unsurprisingly, the most waterward portions of plots experienced greatest elevation loss. Reef presence fostered both higher plant survival and higher shoot density, while clonal expansion was greater at control sites. Shoot density decreased over the course of the study, while clonal expansion peaked in late July before also declining. Overall, any effect of fertilization was swamped by the high hydrodynamic stress impacting transplanted vegetation. Conventional restoration approaches are often ineffective in areas of high stress. I highlight the ways in which deliberate decisions regarding oyster reef substrate and siting can maximize protection to salt marsh edges, and critical considerations for future research regarding mitigation of nutrient over-enrichment in threatened salt marsh systems. Harnessing of inter-specific facilitation between native foundation species represents a promising avenue to restore and protect these critical habitats.
Keywords: inter-specific facilitation; Restoration ecology--North Carolina--Beaufort; Coastal zone management--North Carolina--Beaufort; Environmental protection--North Carolina-- Beaufort; Salt marsh restoration--North Carolina--Beaufort